Immunometabolism of Tregs: mechanisms, adaptability, and therapeutic implications in diseases - Lu, Yuming; Wang, Yifan; Ruan, Tiantian; Wang, Yihan; Ju, Linling; Zhou, Mengya; Liu, Luyin; Yao, Dengfu; Yao, Min (Frontiers in Immunology, 2025)
Immunometabolism is an emerging field that explores the intricate interplay between immune cells and metabolism. Regulatory T cells (Tregs), which maintain immune homeostasis in immunometabolism, play crucial regulatory roles. The activation, differentiation, and function of Tregs are influenced by various metabolic pathways, such as the Mammalian targets of rapamycin (mTOR) pathway and glycolysis. Correspondingly, activated Tregs can reciprocally impact these metabolic pathways. Tregs also possess robust adaptive capabilities, thus enabling them to adapt to various microenvironments, including the tumor microenvironment (TME). The complex mechanisms of Tregs in metabolic diseases are intriguing, particularly in conditions like MASLD, where Tregs are significantly upregulated and contribute to fibrosis, while in diabetes, systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA), they show downregulation and reduced anti-inflammatory capacity. These phenomena suggest that the differentiation and function of Tregs are influenced by the metabolic environment, and imbalances in either can lead to the development of metabolic diseases. Thus, moderate differentiation and inhibitory capacity of Tregs are critical for maintaining immune system balance. Given the unique immunoregulatory abilities of Tregs, the development of targeted therapeutic drugs may position them as novel targets in immunotherapy. This could contribute to restoring immune system balance, resolving metabolic dysregulation, and fostering innovation and progress in immunotherapy.